Madagascar Economic Update, October 2017 : Coping with Shocks - World Bank (Washington, DC, 2017)
The World Bank is sharing the seventh edition of the Economic Update of Madagascar, which presents our analysis for the period up to the beginning of October 2017 and provides our medium-term economic outlook. Despite a challenging start due to two climatic shocks, we project growth at 4.1 percent in 2017, a continuation of the positive trend from last year. Key growth drivers in 2017 are expected to remain as services-related activities, construction works to partly support the reconstruction efforts from the natural disasters, and strong demand for Malagasy textiles from abroad. The severe drought in the first few months of the year affected agricultural activities and reduced hydroelectric power supply. Output for key staples such as rice fell, contributing to higher inflation and an increase in food imports. And in March 2017, Madagascar experienced its most severe cyclone in 13 years, where losses were estimated at US$ 400 million, equivalent to approximately 4 percent of GDP.